THE PERCEPTIONS OF WINE CONSUMERS REGARDING THE USE OF DIGITAL WINE LISTS IN DIGITALLY ORIENTED RESTAURANTS - Labus, Pero; Lukić Nikolić, Jelena (Economics of Agriculture, 2023)
The aim of this paper is to examine and analyze the perceptions of wine consumers regarding the use of digital wine lists in restaurants. The empirical research was conducted using a specially designed questionnaire, which was completed by 406 respondents from 2020 to 2021. The data analysis applied descriptive statistics, KolmogorovSmirnov test, Levene’s test, and the Kruskal-Wallis H test. The results showed that restaurants with digital wine lists are preferred by consumers who are at the young age group (between the ages of 18 and 35), have no prior knowledge about wine, and visit restaurants frequently (a few times per month). These respondents are willing to recommend digitally oriented restaurants and their services to others. The results and conclusions presented in this research could serve as a foundation for decision-makers and managers in restaurants to consider the introduction of digital wine lists and to improve their restaurant’s attractiveness.